Mood Sensitive Stocks and Sustainable Cross-Sectional Returns During the COVID-19 Pandemic: An Analysis of Day of the Week Effect in the Chinese A-Share Market - ul Ain, Qurat; Azam, Tamoor; Yousaf, Tahir; Zafar, Muhammad Zeeshan; Akhtar, Yasmeen (Frontiers in Psychology, 2021)
This study examines two stock market anomalies and provides strong evidence of the day-of-the-week effect in the Chinese A-share market during the COVID19 pandemic time period. Specifically, we examined the Quality minus Junk (QMJ) strategy return on Monday and Friday. The QMJ factor is similar to the division of speculative and non-speculative stocks described by Birru (2018). Our findings provide evidence that the QMJ strategy gains negative returns on Fridays for both anomalies because the junk side is sensitive to an elevated mood and, thus, performs better than the quality side of portfolios on Friday. Our findings are also consistent with the theory of investor sentiment which asserts that investors are more optimistic when their mood is elevated, and generally individual mood is better on Friday than on other days of the week. Therefore, the speculative stocks earned higher sustainable stock returns during higher volatility in Chinese market due to COVID19. Intrinsically, new evidence emerges with an inclined strategy to invest in speculative stocks on Fridays during the COVID19 pandemic to gain sustainable excess returns in the Chinese A-share market.